Extended-spectrum beta-lactamase-producing Pseudomonas aeruginosa in camel in Egypt: potential human hazard - Mahmoud Elhariri; Dalia Hamza; Rehab Elhelw; Sohad M. Dorgham (BMC, 2017)
Abstract Background The rapid increase of extended-spectrum beta-lactamase (ESBL) producing bacteria are a potential health hazard. Development of antimicrobial resistance in animal pathogens has serious implications for human health, especially when such strains could be transmitted to human. In this study, the antimicrobial resistance due to ESBL producing Pseudomonas aeruginosa in the camel meat was investigated. Methods In this study meat samples from 200 healthy camels at two major abattoirs in Egypt (Cairo and Giza) were collected. Following culture on cetrimide agar, suspected P. aeruginosa colonies were confirmed with a Vitek 2 system (bioMe´rieux). P. aeruginosa isolates were phenotypically identified as ESBL by double disk synergy test. Additionally antimicrobial susceptibility testing of ESBL producing P. aeruginosa isolates were done against 11 antimicrobial drugs and carried out by disk diffusion method. The ESBL genotypes were determined by polymerase chain reaction according to the presence of the bla PER-1, bla CTX-M, bla SHV, and bla TEM. Results Pseudomonas aeruginosa was isolated from 45 camel meat sample (22.5%). The total percentage of ESBL producing P. aeruginosa was 45% (21/45) from camel meat isolates. Antibiogram results revealed the highest resistance was for c, ceftriaxone and rifampicin followed by cefepime and aztreonam. The prevalence rates of β-lactamase genes were recorded (bla PER-1 28.5%, bla CTX-M 38%, bla SHV 33.3% and bla TEM 23.8%). Conclusions This study illustrates the presence of high rates of ESBL-P. aeruginosa in camels that represents an increasing alarming for the risk of transmission to human and opens the door for current and future antibiotics therapy failure. Livestock associated ESBL-P. aeruginosa is a growing disaster, therefore, attention has to be fully given to livestock associated ESBL-bacteria which try to find its way to human beings.